EXTRACTION, POTENTIATION AND QUANTITATIVE DETERMINATION OF RESVERATROL FROM SOUTH AFRICAN RED ’CONCORD’ GRAPE PUMICE USING ASSAY-GUIDED METHODS - Igwe, C.; Eloff, J. N.; van Brummelen, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Resveratrol (trans-3, 5, 4’-trihydroxystilbene) was extracted, potentiated and quantitatively determined from fresh frozen red ’concord’ grape pumice using assay-guided methods of column chromatography (CC), thin layer chromatography (TLC) and High Performance Liquid Chromatography (HPLC). Fresh frozen samples of red ’concord grape pumice were milled in the frozen state and subjected to acid hydrolysis for 30 minutes at 60 ÂºC and resveratrol extracted with 96% absolute ethanol. The extract (10 mg/mL) was filtered and concentrated under vacuum at 40 ÂºC. Samples of the concentrated extract were loaded in two different columns with Diaion HP-20 and Dowex-SD-2 adsorbent resins. Five fractions each were collected using 100% ethanol, ethanol: acetone mixtures (70:30, 60:40, 50:50) and 100% acetone. Each of the fractions was loaded on aluminum back silica gel TLC plates, developed in an Ethylacetate: Methanol: Water chromatographic tank and spotted. The TLC spots showed that the fractions Ethanol: acetone (50:50) and 100% acetone in the Dowex-SD-2 column contained resveratrol and 100% acetone in the column with Diaion HP-20 also contained resveratrol. These fractions with resveratrol were then analysed using HPLC and the result showed that ethanol: acetone (50:50) fraction contained 0.0222 mg/mL resveratrol, 100% acetone fraction contained 0.465mg/mL resveratrol, for Dowex SD-2 column and for the Diaion HP-20 column, 100% acetone fraction contained 0.221mg/mL resveratrol. The results of the studies were better than the reports of yields quoted in literature.